2020
DOI: 10.1371/journal.pone.0232921
|View full text |Cite
|
Sign up to set email alerts
|

Yap activation in irradiated parotid salivary glands is regulated by ROCK activity

Abstract: Radiotherapy plays a major role in the curative treatment of head and neck cancer, either as a single modality therapy, or in combination with surgery or chemotherapy, or both. Despite advances to limit radiation-induced side-effects, the major salivary glands are often affected. This frequently leads to hyposalivation which causes an increased risk for xerostomia, dental caries, mucositis, and malnutrition culminating in a significant impact on patients’ quality of life. Previous research demonstrated that lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 54 publications
(126 reference statements)
1
13
0
Order By: Relevance
“…A reduction in the interaction between E-cadherin and β-catenin leads to actin filament fragmentation in mouse parotid glands 7–30 days post-IR due to increased rho-associated kinase (ROCK) signaling that can be reversed by post-IR IGF-1 treatment [ 50 ]. Further evaluation of this pathway showed that ROCK signaling leads to activation and nuclear translocation of the transcriptional regulator Yes-associated protein (Yap) that is modulated by ROCK inhibition or IGF-1 treatment [ 64 ]. Yap activity is typically beneficial in injury models, although in salivary glands increased activation of Yap is seen in subsets of stem and progenitor cells, as well as the entire acinar compartment in parotid glands at days 5–30 post-IR in models that do not restore salivary function [ 55 , 64 ].…”
Section: Animal Models Provide Mechanistic Insight Into Radiation-mentioning
confidence: 99%
See 3 more Smart Citations
“…A reduction in the interaction between E-cadherin and β-catenin leads to actin filament fragmentation in mouse parotid glands 7–30 days post-IR due to increased rho-associated kinase (ROCK) signaling that can be reversed by post-IR IGF-1 treatment [ 50 ]. Further evaluation of this pathway showed that ROCK signaling leads to activation and nuclear translocation of the transcriptional regulator Yes-associated protein (Yap) that is modulated by ROCK inhibition or IGF-1 treatment [ 64 ]. Yap activity is typically beneficial in injury models, although in salivary glands increased activation of Yap is seen in subsets of stem and progenitor cells, as well as the entire acinar compartment in parotid glands at days 5–30 post-IR in models that do not restore salivary function [ 55 , 64 ].…”
Section: Animal Models Provide Mechanistic Insight Into Radiation-mentioning
confidence: 99%
“…Further evaluation of this pathway showed that ROCK signaling leads to activation and nuclear translocation of the transcriptional regulator Yes-associated protein (Yap) that is modulated by ROCK inhibition or IGF-1 treatment [ 64 ]. Yap activity is typically beneficial in injury models, although in salivary glands increased activation of Yap is seen in subsets of stem and progenitor cells, as well as the entire acinar compartment in parotid glands at days 5–30 post-IR in models that do not restore salivary function [ 55 , 64 ]. In contrast, post-IR IGF-1 treatment reduces Yap activity and improves salivary gland function in a PKCζ-dependent manner [ 55 , 64 ].…”
Section: Animal Models Provide Mechanistic Insight Into Radiation-mentioning
confidence: 99%
See 2 more Smart Citations
“…The functional recovery of saliva production normally achieved by the administration of IGF-1 after IR [ 91 ] was absent under Pkcζ ablation. Similarly, 5 Gy of head/neck-IR of FVB mice resulted in higher nuclear Yap1 localization in the acinar compartment while no changes were reported in cells of major ducts [ 92 ]. IGF-1 treatment of irradiated mice restored Yap1 nuclear localization to normal, suggesting that the SG functional recovery promoted by IGF-1 is a consequence of the reduction of Yap1 nuclear translocation.…”
Section: Signaling Pathways That Contribute To Sc Radiation Responmentioning
confidence: 99%